Role of arginine supplementation on muscular metabolism and flesh quality of Pacific white shrimp (Litopenaeus vannamei) reared in freshwater - Li, Meifeng; Wen, Hua; Huang, Feng; Wu, Meili; Yu, Lijuan; Jiang, Ming; Lu, Xing; Tian, Juan (Frontiers in Nutrition, 2022)
It is no doubt that the improvement of flesh quality of Pacific white shrimp (Litopenaeus vannamei) reared in freshwater contributes to its development potential in aquaculture. In this study, we aimed to explore the effect of arginine supplementation on the flesh quality of L. vannamei reared in freshwater and its mechanism. L. vannamei were randomly fed with three diets for 56 days, of which arginine level was 10.15 g kg-1 (arginine-deficient diet), 21.82 g kg-1 (arginine-optimal diet), and 32.46 g kg-1 (arginine-excessive diet), respectively. Each diet was randomly assigned to triplicate tanks, and each tank was stocked with 35 shrimps (initial weight: 1.70 ± 0.02 g). Results showed the arginine-optimal diet increased the weight gain, flesh percentage, crude protein and flavor amino acid contents in muscle, and improved the flesh hardness by conversing fast myofibers to slow myofibers, increasing myofiber density and myofibrillar length, and promoting ornithine and collagen synthesis. The arginine-optimal diet influenced the purine metabolic pathway by reducing hypoxanthine, xanthine, and inosine contents. Ornithine, citrulline, and glutamate were identified as the key metabolites affecting flesh quality traits after arginine treatments. Only increasing the levels of dietary arginine did not result in an increase in endogenous creatine synthesis in muscle and hepatopancreas. Overall, the arginine-optimal diet improved the flesh quality traits of L. vannamei reared in freshwater due to the enhanced muscular hardness, protein deposition, and flavor, which may be contributing to the transformation of muscle fiber type and increase in protein synthesis by the metabolites of arginine (ornithine, citrulline, and glutamate).